2009
DOI: 10.1007/s10152-009-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of two Portuguese populations of the pullet carpet shell Venerupis senegalensis, based on RAPD markers: contribution to a sustainable restocking program

Abstract: The pullet carpet shell Venerupis senegalensis (=V. pullastra) is a commercially important species in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The genetic diversity of N. magellanica in each locality was relatively high and did not vary considerably among sampling sites (mean P% = 78.48; mean I = 0.36). The Shannon's diversity index values are comparable to the ones obtained in two Portuguese localities of the commercial pullet carpet shell Venerupis senegalensis (I = 0.339-0.361; Joaquim et al, 2010) using RAPD dominant markers and are much higher than those reported for two barnacle species using ISSRs (I of Chthamalus stellatus = 0.147-0.222; I of Tesseropora atlantica = 0.111-0.190; Pannacciulli et al, 2009). The authors discussed these genetic variability values in relation to the population size and lifespan of the larval stage, being higher in large populations with extensive larval dispersal than in small populations with short larval lifespan.…”
Section: Discussionsupporting
confidence: 74%
“…The genetic diversity of N. magellanica in each locality was relatively high and did not vary considerably among sampling sites (mean P% = 78.48; mean I = 0.36). The Shannon's diversity index values are comparable to the ones obtained in two Portuguese localities of the commercial pullet carpet shell Venerupis senegalensis (I = 0.339-0.361; Joaquim et al, 2010) using RAPD dominant markers and are much higher than those reported for two barnacle species using ISSRs (I of Chthamalus stellatus = 0.147-0.222; I of Tesseropora atlantica = 0.111-0.190; Pannacciulli et al, 2009). The authors discussed these genetic variability values in relation to the population size and lifespan of the larval stage, being higher in large populations with extensive larval dispersal than in small populations with short larval lifespan.…”
Section: Discussionsupporting
confidence: 74%
“…Aveiro is a shallow lagoon system with high tidal flow that allows a large water renovation. This may promote larval drift to the coastal waters (Joaquim et al 2010) and be responsible for larvae dispersal, preventing genetic differentiation. Although Ferrol is also located northwest of the Iberian Peninsula, it showed significant differences to all other four Iberian localities analyzed but Corcubión.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the genetic plasticity and genetic similarity of the two populations reported by Joaquim et al(2010), and which make the Ria de Aveiro V. senegalensis population a genetically viable broodstock for intensive hatchery production of juveniles, the extended spawning period of this V. senegalensis population has interesting implications for the implementation of profitable aquaculture. This extended natural spawning period implies that manipulation of broodstock in terms of conditioning, which should be initiated in late summer, would be relatively easy.…”
Section: Discussionmentioning
confidence: 99%